Ancient Roman nano-technology: Insight into the manufacture of mosaic tesserae opacified by calcium antimonate. Issue 14 (November 2018) - Drünert, Ferdinand; Palamara, Eleni; Zacharias, Nikolaos; Wondraczek, Lothar; Möncke, Doris
Abstract: Opaque mosaic glass tesserae containing calcium antimonates from Ancient Messene, Greece (1st–4th century CE) were investigated by scanning electron microscopy, Raman spectroscopy and X-ray diffraction. Both trigonal CaSb2 O6 and cubic Ca2 Sb2 O7, with crystallite diameters below 1 μm, were identified as opacifying agents. To better understand ancient technologies, we prepared model glasses that were opacified by crystallisation via a secondary heat treatment, by direct crystallisation during the melting process, or by the addition of pre-reacted calcium antimonate to a base glass. We found that direct crystallisation replicated the antique glass artefacts most accurately. We demonstrated that 0.2 wt% of nucleating agents like TiO2 and SnO2 already exert significant influence on the crystallisation behaviour of calcium antimonates. Secondary scattering centres such as silica and carbonates contribute to the optical appearance. Concurrently, we reproduced opaque white glass ceramics in a reconstructed, wood-fired, Roman-type glass furnace built by Wiesenberg (2014).